Current immunotherapeutic approaches to diffuse intrinsic pontine glioma - Lin, Catherine; Smith, Christian; Rutka, James (Frontiers in Genetics, 2024)
Diffuse intrinsic pontine glioma (DIPG) is an aggressive brain tumour that occurs in the pons of the brainstem and accounts for over 80% of all brainstem gliomas. The median age at diagnosis is 6-7 years old, with less than 10% overall survival two years after diagnosis and less than 1% after five years. DIPGs are surgically inaccessible, and radiation therapy provides only transient benefit, with death ensuing from relentless local tumour infiltration. DIPGs are now the leading cause of brain tumour deaths in children, with a societal cancer burden in years of life lost (YLL) of more than 67 per individual, versus approximately 14 and 16 YLL for lung and breast cancer respectively. More than 95 clinical drug trials have been conducted on children with DIPGs, and all have failed to improve survival. No single or combination chemotherapeutic strategy has been successful to date because of our inability to identify targeted drugs for this disease and to deliver these drugs across an intact blood-brain barrier (BBB). Accordingly, there has been an increased focus on immunotherapy research in DIPG, with explorations into treatments such as chimeric antigen receptor T (CAR-T) cells, immune checkpoint blockades, cancer vaccines, and autologous cell transfer therapy. Here, we review the most recent advances in identifying genetic factors influencing the development of immunotherapy for DIPG. Additionally, we explore emerging technologies such as Magnetic Resonance guided Focused Ultrasound (MRgFUS) in potential combinatorial approaches to treat DIPG.